Cultural Resistance and Democratic Imagination in Colonial Indonesia: A Literary Analysis of Pantun - Elisabeth Purba; Rosmawaty Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
Colonial rule in the Indonesian archipelago not only restructured political and economic systems but also sought to reshape local cultural values and modes of expression. Within this context, traditional literary forms played an important role in preserving cultural identity and articulating responses to colonial domination. One such form is pantun, a Malay poetic genre that conveys meaning through metaphor, parallelism, and indirect expression. This study examines how the pantun High Power, Unformed Resistance represents power, resistance, and democratic imagination during the colonial period. The research aims to explore how culturally grounded notions of authority and opposition are articulated through poetic discourse, and how pantun functions as a medium of subtle resistance and ethical governance. The study adopts a qualitative interdisciplinary methodology that combines close textual analysis with perspectives from postcolonial theory and cultural studies. The pantun is analyzed as both a literary text and a socio cultural artifact situated within the historical experience of colonial Indonesia. The findings reveal that power is constructed as moral and cultural authority rather than coercive domination, while resistance emerges as indirect, adaptive, and sustained through cultural continuity. The pantun also encodes democratic values such as consensus, balance, and communal responsibility, reflecting indigenous conceptions of governance. These findings suggest that pantun should be understood not merely as folklore but as a significant site of political meaning. The study contributes to literary and postcolonial scholarship by demonstrating how traditional poetic forms participate in the negotiation of power and the imagination of culturally grounded democracy under colonial rule.